PENGARUH POLA ASUH ORANG TUA TERHADAP PERKEMBANGAN SOSIAL ANAK AUTIS DI SLB NEGERI PEMBINA MAKASSAR DAN SLB NEGERI 1 MAKASSAR TAHUN 2020 - Nurul Rahmadiani; Rosdiana Rahim; Rini Fitriani (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Autism is a disorder that causes children to have problems with their social environment. Its influence influences language development. The first social environment is the family which plays an important role in children's development. While parenting is divided into three patterns of parenting democracy, authoritarian parenting, and permissive parenting. Specifically, the purpose of this study was to study parenting related to the social development of children with autism.Aim. The research aims to determine the influence of parenting patterns on the social development of autistic children. Methods. This research uses a quantitative method using causal somperative. Results. Samples were taken using total sampling, namely all participants of autistic children in SDLB Negeri Pembina and SDLB Negeri 1 Makassar. The results obtained by linear regression, simple, produce a regression coefficient of 0.797 with a significance of 0.034 α α (0.05) for authoritarian parenting -0.040 and 0,000 ≤ α (0.05) for permissive parenting -0,861 ≤ α (0.018) ). the results of this study are expected to make the community and autistic children in accordance with the requirements and can be used for further research. Conclusion. This study shows that there is an effect of parenting on the social development of autistic children.